University Students’ Motives-for-Physical-Activity Profiles: Why They Practise and What They Get in Terms of Psychological Need Satisfaction - Valenzuela, Rafael; Codina, Nuria; Pestana, José Vicente (Frontiers in Psychology, 2021)
Physical Activity (PA) is an important habit for overall health and quality of life, but it tends to recede as young adults transition from high school into university. The present study sought to understand, in the case of university students that still practice PA, their motives for PA, and their relationships with Psychological Need Satisfaction (PNS) and characteristics of practice regularity (frequency, duration, team, competitive, coach, league, federation, and type of day of the week for PA). Participants were 423 university students who reported to practise PA (203 identified as men, 191 as women, 29 did not report gender), ages ranging from 18 to 30 years old (M = 19.91, SD = 1.97). Measures assessing motives for PA, PNS, and PA characteristics were completed. Hierarchical, followed by iterative, cluster analysis was used and four naturally occurring groupings of university students were identified based on their motives for PA: one extrinsic-motives cluster (with both extrinsic motives –fitness and appearance– above the mean); one all-motives cluster (with all five motives above the mean), one intrinsic-motives cluster (with all three intrinsic motives – enjoyment, competence, social – above the mean); and one low-motives cluster (with all motives below the mean). Groupings were compared in terms of the characteristics of their practice regularity (frequency, duration, competition, team, coach, league, federation, type of day of the week used for PA) and their levels of PNS (of the needs for autonomy, competence, and relatedness in PA). Significant between-groups differences were observed in duration of single principal PA sessions, minutes per week practising main PA, total PA minutes per week, and type of day of the week used for PA. Number of days per week devoted to the principal PA and number of total PAs practised were similar across all four clusters. With regards to between-groups differences in psychological need satisfaction in PA by cluster, these analyses showed the existence of four clearly distinguishable naturally occurring groupings based on motives for PA, which gives researchers and practitioners the possibility to analyse and implement tailored interventions aimed at promoting PA among university students.